Hipersuperfícies imersas em Hn+1 (-1) com curvatura média constante e bordo planar - Lira, Jorge Herbert Soares de (1997)
In this monograph, we intend to present two results that establish sufficient conditions for a manifold to "inherit" the symmetries of its boundary. Stability theorems found in *Stability of hypersurfaces of constant mean curvature in Riemannian manifolds* are used, applied to the particular situation in which the ambient space has constant sectional curvature.